Nuclear moonlighting of cytosolic glyceraldehyde-3-phosphate dehydrogenase regulates Arabidopsis response to heat stress - Sang-Chul Kim (Nature Portfolio, 2020)
Stress conditions can induce translocation of glyceraldehyde-3-phosphate dehydrogenase (GAPC) to the nucleus. Here Kim et al. show that in Arabidopsis, GAPC can interact with the NF-YC transcription factor subunit, enhance expression of heat-inducible genes and promote heat tolerance.